1977
DOI: 10.1152/ajpcell.1977.233.1.c14
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics of skeletal muscles of dogs and cats

Abstract: Our purpose was to determine if physiological characteristics of skeletal muscles of dogs and cats are related to their histochemical and biochemical characteristics. Maximum oxygen consumption (VO2max) and blood flow (Q) at VO2max were determined for in situ muscles of dogs and cats. Compared to cat muscles, dog muscles per unit mass had higher succinate oxidase activities, VO2max's, and Q's at VO2max's. There are positive relationships between Q at VO2max and VO2max and between VO2max and succinate oxidase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 20 publications
5
57
0
Order By: Relevance
“…1) The contraction pattern was obviously unphysiological (see above). 2) Fiber type composition of dog gastrocnemius muscle [predominantly constituted by type I and type IIa fibers (22)] is different compared with that of human muscle 5although the difference is small if endurance athletes are considered [e.g., see the review by Saltin and Gollnick (28)]6. 3) Resting Q to muscle, in control conditions, was 6-to 10-fold higher than those observed in humans (e.g., see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…1) The contraction pattern was obviously unphysiological (see above). 2) Fiber type composition of dog gastrocnemius muscle [predominantly constituted by type I and type IIa fibers (22)] is different compared with that of human muscle 5although the difference is small if endurance athletes are considered [e.g., see the review by Saltin and Gollnick (28)]6. 3) Resting Q to muscle, in control conditions, was 6-to 10-fold higher than those observed in humans (e.g., see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…All excised muscle tissue was immediately frozen (Ͻ2 s) by submersion in liquid nitrogen. Biochemical and histochemical analyses have shown that the canine gracilis muscle (typically weighing ϳ25 g in a 1-yr-old beagle dog) has a fiber type composition of ϳ40% type I and ϳ60% type IIa fibers (22). The canine gracilis muscle is comparable in fiber type composition to human skeletal muscle, and the model used here allows multiple biopsy sampling without a severe detriment to contractile function (27, 28, 34 -36).…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this study was to determine whether a 33-electrode spiral cuff could be used to selectively collect the sensory information from the sciatic nerve of a dog. In particular, we wanted to know if an ENG could be recorded selectively from nerve fibers within superficial regions of a dog's sciatic nerve innervating mainly muscle spindles and Golgi tendon organs of the tibialis anterior (TA) and gastrocnemius (GM) muscles [19].…”
mentioning
confidence: 99%